SITUATION OF THE UKRAINIAN DIASPORA IN RUSSIAN FEDERATION IN THE CONTEXT OF THE KREMLIN'S REVANCHIST POLICY TOWARDS UKRAINE - Bezsmertna, Natalia (Київський національний університет імені Тараса Шевченка, 2021)
The situation of the Ukrainian diaspora in the Russian Federation (hereinafter – the Russian Federation) in the conditions of the Kremlin's revenge policy towards Ukraine and Ukrainians is analyzed. The policy of the Russian Federation concerning the gradual and purposeful absorption of the non-Russian peoples of the Russian Federation and their final transformation into Russians ("Russians") is described. The place of the Ukrainian diaspora in modern Russia is comprehended, based on the data of population censuses (1989, 2002, 2010). It was found that the Russian Federation pursues a strict aggressive policy of assimilation towards the Ukrainian diaspora, imposes its neo-imperial ideology, closes diaspora associations, Ukrainian churches, applies repressive measures against local Ukrainians, in connection with which they are forced to hide their nationality. It was found that as a result of such an assimilation policy of the central government, the Ukrainian diaspora in Russia loses its identity and uniqueness, forgets its native Ukrainian language, history, traditions and customs, gradually assimilating and merging with the Russian people. It is noted that the Ukrainian state needs to introduce a new effective Program of interaction with foreign Ukrainians, as the Program (2018 – 2020) has lost its relevance. It is proposed to include in the new Program information about various events (congresses, conferences, round tables, seminars, festivals, film screenings), attending which the Ukrainian diaspora from Russia will get acquainted with the Ukrainian language, history, science, literature, customs and traditions, songs, movies ( movies, documentaries, cartoons). It is emphasized that now the Russian authorities, under the guise of a pandemic, do not allow the Ukrainian diaspora to enter Ukraine, so there is a need to involve them in online events (online conferences, webinars, etc.) held in Ukraine, as well as to create YouTube has various channels with Ukrainian content (Ukrainian songs, customs, traditions, legends, lessons in the Ukrainian language, history, etc.) to promote all things Ukrainian on the Internet.

Проаналізовано становище української діаспори у Російській Федерації (далі – РФ) в умовах політики реваншу Кремля щодо України й українців. Охарактеризовано політику РФ відносно поступового й цілеспрямованого поглинання неросійських народів РФ й остаточне перетворення їх у росіян («русских»).Осмислено місце української діаспори в сучасній РФ, ґрунтуючись на даних переписів населення (1989 р., 2002 р, 2010 р.). З‘ясовано, що РФ проводить жорстку агресивну політику асиміляції щодо української діаспори, нав‘язує свою неоімперську ідеологію, закриває діаспорні об‘єднання, українські церкви, застосовує репресивні заходи проти місцевих українців, у зв‘язку з чим, вони змушені приховувати свою національність.Виявлено, що внаслідок такої асиміляційної політики центральної влади українська діаспора у РФ втрачає свою самобутність та неповторність, забуває свою рідну українську мову, історію, традиції і звичаї, поступово асимілюючись і зливаючись з російським народом. Зазначено, що з боку Української держави потрібно запровадити нову дієву Програму взаємодії із зарубіжними українцями, оскільки Програма (2018 – 2020) втратила свою актуальність. Запропоновано включити у нову Програму інформацію про різні заходи (конгреси, конференції, круглі столи, семінари, фестивалі, кінопокази), відвідуючи які українська діаспора з РФ буде знайомитися з українською мовою, історією, наукою, літературою, звичаями та традиціями, піснями, фільмами (кінофільмами, документальними фільмами, мультфільмами). Наголошено, що зараз влада РФ, прикриваючись пандемією, не надає дозвіл на в‘їзд українській діаспорі РФ в Україну, тому є потреба залучати її до онлайн-заходів (онлайн-конференції, вебінари тощо), які проводяться в Україні, а також створювати на Ютубі різноманітні канали з українським контентом (українські пісні, звичаї, традиції, легенди, заняття з української мови, історії і т.ін.) для популяризації всього українського у мережі Інтернет.
CТАНОВИЩЕ УКРАЇНСЬКОЇ ДІАСПОРИ У РОСІЙСЬКІЙ ФЕДЕРАЦІЇ В УМОВАХ РЕВАНШИСТСЬКОЇ ПОЛІТИКИ КРЕМЛЯ ЩОДО УКРАЇНИ
Keywords: Ukraine; Ukrainians; the Ukrainian diaspora in the Russian Federation; the assimilation policy of the RF; russification; the Ukrainian language; Ukrainian ethnocultural processes; the Russian-Ukrainian hybrid war; the policy of revenge of the RF; Україна; українці; українська діаспора у Російській Федерації; асиміляційна політика РФ; зросійщення; українська мова; українські етнокультурні процеси; російсько-українська гібридна війна; політика реваншу РФ